M. Syukron Ali Amiruddin - Baraz Yoechva Alfaiz, M. Syukron Ali Amiruddin, (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2023)
Abstract: The title does not directly compare the Quran with science and technology, because from the beginning, it encouraged Muslims to advance both. Much research has recently been conducted on the interrelation between the Quran, science, and technology. The two are so different entities that it is difficult to compare directly. However, there are different perspectives when looking for relationships between them in the context of universe events, religious practice, or everyday life. The Quran, which became the holy book of Muslims, gave truth to science to ensure scientific certainty. The interpretation of Quranic verses related to the events of the universe is constantly expanding. Science has always played a role in their search for new, authentic knowledge. Both fields aim to find patterns of order that correspond to existing truths. This research focuses on the relationship of the Quran with Science and Technology. This research uses qualitative methods with the type of literature study research.Keywords: Korelasi, Al-Qur'an, Modern Science